2017
DOI: 10.18202/jamal.2017.08.7060
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kinerja Bank Islam

Abstract: Determinan Kinerja Bank Islam. Studi ini bertujuan menguji pengaruh sistem pengukuran kinerja strategis dan pengendalian interaktif terhadap kinerja bank Islam. Pengumpulan data dilakukan dengan mail survey kepada bank Islam di Jawa Timur dan diolah menggunakan Partial Least Square. Hasil studi membuktikan bahwa pengendalian inter aktif dan sistem pengukuran kinerja strategis mampu memfasilitasi orga nisasi. Selain itu, kapabilitas memberikan andil dalam meningkatkan kinerja organisasi. Hal ini menjadi penting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In his research, Khan (2013) and Zarrouk, Jedi dia, & Moualhi (2016) revealed that there are many problems have to be solved by the Islamic banks in their operations, especial ly in the strict adherence to the values of sharia which should be inherent and inte gral values to these model financial institu tions. Even in another study conducted by Abusharbeh (2011) and Aprilia, Rosidi, & Saraswati (2017), noted that Islamic bank ing is seen only trying to chase conventional targets such as efficiency and profitability, so even though the products of Islamic bank ing seem to follow the rules of sharia but they lose the ethics that should be contained in the sharia products. Islamic banking is promising and has a positive side in the pro fitability and liquidity aspects, but still have different conditions when compared to the conventional banking (Tunc, 2014;Sufian, 2010).…”
mentioning
confidence: 99%
“…In his research, Khan (2013) and Zarrouk, Jedi dia, & Moualhi (2016) revealed that there are many problems have to be solved by the Islamic banks in their operations, especial ly in the strict adherence to the values of sharia which should be inherent and inte gral values to these model financial institu tions. Even in another study conducted by Abusharbeh (2011) and Aprilia, Rosidi, & Saraswati (2017), noted that Islamic bank ing is seen only trying to chase conventional targets such as efficiency and profitability, so even though the products of Islamic bank ing seem to follow the rules of sharia but they lose the ethics that should be contained in the sharia products. Islamic banking is promising and has a positive side in the pro fitability and liquidity aspects, but still have different conditions when compared to the conventional banking (Tunc, 2014;Sufian, 2010).…”
mentioning
confidence: 99%
“…Islamic and conventional banks have fundamentally different principles, concepts and practices in politics, ethics and moral economics. The difference should be the competitiveness of Islamic banks to strengthen distribution equity and economic growth based on real sector (Aprilia et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In corporate governance, the Sharia Supervisory Board in Islamic banks is the party that can improve Sharia compliance (Muhammad, Annuar, Taufik, & Nugraheni, 2021) and social activity (Boudawara et al, 2023). SSB has a monitoring function, so the size of SSB will affect the effectiveness of SSB in monitoring and will further improve company performance (Aprilia et al, 2017). SSB is the most determining factor in ISR disclosure (Mukhibad, 2018).…”
Section: Sharia Supervisory Boardmentioning
confidence: 99%